Overexpression of MRP1/ABCC1, Survivin and BCRP/ABCC2 Predicts the Resistance of Diffuse Large B-Cell Lymphoma to R-CHOP Treatment - Mandić, Danijela; Nežić, Lana; Amdžić, Ljiljana; Vojinović, Nataša; Gajanin, Radoslav; Popović, Miroslav; Đeri, Jugoslav; Balint, Milena Todorović; Dumanović, Jelena; Milovanović, Zoran; Grujić-Milanović, Jelica; Škrbić, Ranko; et al. (Cancers, 2023)
BACKGROUND: Approximately 40% of patients with diffuse large B-cell lymphoma (DLBCL) experience treatment resistance to the first-line R-CHOP regimen. ATP binding cassette (ABC) transporters and survivin might play a role in multidrug resistance (MDR) in various tumors. The aim was to investigate if the coexpression of ABC transporters and survivin was associated with R-CHOP treatment response. METHODS: The expression of Bcl-2, survivin, P-glycoprotein/ABCB1, MRP1/ABCC1, and BCRP/ABCC2 was analyzed using immunohistochemistry in tumor specimens obtained from patients with DLBCL, and classified according to the treatment response as Remission, Relapsed, and (primary) Refractory groups. All patients received R-CHOP or equivalent treatment. RESULTS: Bcl-2 was in strong positive correlation with clinical parameters and all biomarkers except P-gp/ABCB1. The overexpression of MRP1/ABCC1, survivin, and BCRP/ABCC2 presented as high immunoreactive scores (IRSs) was detected in the Refractory and Relapsed groups (p < 0.05 vs. Remission), respectively, whereas the IRS of P-gp/ABCB1 was low. Significant correlations were found among either MRP1/ABCC1 and survivin or BCRP/ABCC2 in the Refractory and Relapsed groups, respectively. In multiple linear regression analysis, ECOG status along with MRP1/ABCC1 or survivin and BRCP/ABCG2 was significantly associated with the prediction of the R-CHOP treatment response. CONCLUSIONS: DLBCL might harbor certain molecular signatures such as MRP1/ABCC1, survivin, and BCRP/ABCC2 overexpression that can predict resistance to R-CHOP.
Keywords: survivin; non-Hodgkin lymphoma; multidrug resistance; BCRP/ABCC2; MRP1/ABCC1